2022
DOI: 10.1155/2022/1489841
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Alleviates Neuropathic Pain through Regulating miR-206-3p Targeting BDNF after CCI

Abstract: Background. Electroacupuncture (EA) has benefits for neuropathic pain. However, the underlying mechanisms are still unknown. The current study explores the underlying mechanisms of EA in neuropathic pain of chronic constriction injury (CCI) rats. Material/Methods. Overall, 126 Sprague-Dawley (200-250 g) rats were divided into nine groups randomly: the sham-operated, CCI, CCI+EA, CCI+sham EA, CCI+NS, CCI+AAV-NC, CCI+AAV-miR-206-3p, CCI+EA+NS, and CCI+EA+AAV-miR-206-3p groups. The animals were sacrificed 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Research findings have provided evidence for the regulatory role of miR-206-3p as an upstream regulator of Bdnf. The inhibition of miR-206-3p has been shown to lead to the increased expression of Bdnf [ 52 ]. Our study discovered a novel hetero-lncRNA molecule, lncRNA-ENSRNOT00022622, through sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Research findings have provided evidence for the regulatory role of miR-206-3p as an upstream regulator of Bdnf. The inhibition of miR-206-3p has been shown to lead to the increased expression of Bdnf [ 52 ]. Our study discovered a novel hetero-lncRNA molecule, lncRNA-ENSRNOT00022622, through sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A list of microRNAs found to degrade BDNF mRNA transcripts in oncology research is as follows: miR-10a, miR-22, miR-204, miR-107, miR-382, miR-496, miR-497, miR-584, miR-744, miR-26a-1, and miR-26a-2 subtypes [24,28,58,60,72,75,78,88,93,94,96,102,112,125,126,128,132,133,137,190]. The evidence that miR-206 is able to suppress BDNF synthesis in diverse tissues such as the cardiac muscles, the skeletal muscles, and the endothelial tissue elucidates a role for microRNAs in tissue-tissue communication, although their actions might be locally regulated [30,43,45,48,61,92,102,115,120,139,142,169,171,177,191]. Some microRNAs are released from cells by membrane-derived vesicles, lipoproteins, and other ribonucleoprotein complexes and travel through the blood stream reaching recipient cells in distant tissues [192], providing communication between disparate cell types and diverse biological mechanisms and homeostatic pathways.…”
Section: Bdnf By Micrornasmentioning
confidence: 98%
“…miR-584, miR-744, miR-26a-1, and miR-26a-2 subtypes [24,28,58,60,72,75,78,88,93,94,96,102,112,125,126,128,132,133,137,190]. The evidence that miR-206 is able to suppress BDNF synthesis in diverse tissues such as the cardiac muscles, the skeletal muscles, and the endothelial tissue elucidates a role for microRNAs in tissuetissue communication, although their actions might be locally regulated [30,43,45,48,61,92,102,115,120,139,142,169,171,177,191]. MicroRNAs play crucial roles in immunoinflammatory reactions.…”
Section: Bdnf By Micrornasmentioning
confidence: 99%
“…For example, findings from animal research indicate that miR-206-3p regulates BDNF expression through a conserved binding site in its 3 ′ -UTR [160]. Notably, a study demonstrated that electroacupuncture alleviated neuropathic pain induced by chronic constriction injury by increasing miR-206-3p expression and inhibiting BDNF overexpression [161]. However, administration of the miR-206-3p inhibitor partially impaired the analgesic effect of electroacupuncture and the level of BDNF was elevated as well.…”
Section: The Epigenetic Regulation Of Bdnf Expression In Chronic Painmentioning
confidence: 99%